Neutrophil as a multifunctional relay in immune system - I. I. Dolgushin (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
Over the last two or three decades, a concept regarding functional capacities of neutrophilic granulocytes has been remarkably extended owing to new technologies. Neutrophil-related effector potential against infectious agents, including phagocytosis, production of reactive oxygen and nitrogen species, degranulation coupled with the released multiple enzymes and antimicrobial peptides, and the extracellular trap formation have been studied in detail. In particular, it was found that many of the factors used by neutrophils to directly destroy pathogens also exert regulatory effects on other immune cells as well as on neutrophils in an autocrine manner. In addition, activated neutrophils are able to de novo synthesize a range of biologically active molecules. Neutrophil-related immunoregulatory effects on macrophages, dendritic cells, T-lymphocytes and B-lymphocytes may be mediated both via direct intercellular contacts and indirectly through production of cytokines and other biologically active mediators. Ambiguous proactive and suppressive neutrophil-related effects on immune cells evidence about their important role played both in homeostasis and diverse pathologies, particularly in developing malignant tumors. Diverse, even opposing impact exhibited by neutrophilic granulocytes on immune cells and cells in non-lymphoid tissues, point at their functional plasticity and, probably, heterogeneity. Upon that, modality of effects elicited by neutrophils largely depends on surrounding microenvironment while they exit from the circulation. Widely considered as an inf lammatory response inducer, neutrophils are able to simultaneously trigger mechanisms facilitating restriction and resolution of inf lammatory reaction. Using intravital microscopy in animal models, it allowed to discover that neutrophils are able to re-enter circulation after exiting into the extravascular space, thereby challenging a classical concept about a unidirectional neutrophil migration from the blood vessels to body tissue. In addition, evidence that neutrophils can serve as antigen-presenting cells for T cells under certain conditions and are recruited from inf lammatory sites to draining lymph nodes were also obtained. Although a body of the data were obtained in vitro or in animal models, which therefore require to be further examined and verified, it may be unequivocally acknowledged that a neutrophil-related impact is not only limited to innate immunity.